THE INFLUENCE OF HUMAN RESOURCE QUALITY, INTERNAL COMMUNICATION, AND TEAMWORK ON THE PERFORMANCE OF TIPIDKOR MEMBERS A DITRESKRIMSUS POLDA ACEH - Raysahri; Nuzulman; Zikrillah (Journal Informatic, Education and Management (JIEM), 2026)
This study aims to analyze the influence of Human Resource Quality, Internal Communication, and Teamwork on the performance of members of the Tipidkor Unit of the Special Crimes Investigation Directorate (Ditreskrimsus) of the Aceh Regional Police. The study population and sample consisted of 88 respondents, comprising 32 internal respondents and 56 external respondents, using a saturation sampling technique so that the entire population was included as research respondents. The results of the study indicate that the quality of human resources has a positive and significant effect on member performance. Internal communication was also found to have a positive and significant effect on member performance. Conversely, teamwork did not have a significant effect on member performance. Simultaneously, the quality of human resources, internal communication, and teamwork have a significant effect on the performance of members of the Tipidkor Ditreskrimsus of the Aceh Regional Police. These findings indicate that improvements in the performance of members of the Tipidkor Ditreskrimsus of the Aceh Provincial Police are largely determined by the quality of human resources available and the effectiveness of internal communication within the organization. Therefore, efforts to enhance members’ competencies through education and training, as well as strengthening the internal communication system, must be prioritized to support the optimization of member performance. Meanwhile, the aspect of teamwork needs to be evaluated and adapted to the characteristics of investigative tasks so that it can contribute more optimally to the achievement of organizational performance.